Characteristics of ADS target irradiated by 200…400 MeV proton beam - Svistunov, Yu.A.; Kudinovich, I.V.; Golovkina, A.G.; Ovsyannikov, D.A.; Bogdanov, A.A.; Tanchuk, A.V. (Вопросы атомной науки и техники, 2013)
The problems of target choice for compact ADS with reactor thermal power 200…400 MW and 200…400 MeV proton beam are considered. Simulation results of neutron yield from fissile and non-fissile targets are presented and the optimal target sizes are calculated. The principal target design characteristics and its thermal condition are also considered.